Enhancing productivity and nutrition with biofortified pearl millet cultivars - Reddy, P Sanjana; Patroti, Parashuram; Malathi, V M (Indian Farming, 2023)
Food, economic and nutritional securities are equally important to the resource poor farmers relying on pearl millet in marginal environments. Bio-fortified cultivars of pearl millet with higher iron (Fe) and zinc (Zn) content in the grain along with high grain yield are supposed to be the best solution in this context. With the concerted efforts of Indian Council of Agricultural Research (ICAR), Harvest Plus, ICRISAT and State Agricultural Universities, biofortified varieties and hybrids are available in pearl millet. The world first high-Fe pearl millet variety ‘Dhanashakti’ released in 2014 has 71 mg/kg Fe and 2.2 t/ha grain yield. The first set of biofortified hybrids (AHB 1200 Fe and HHB 299) released in 2018 had 73–77 mg/kg Fe, 39–41 mg/kg Zn with more than 3 t/ha of grain yield. With similar levels of grain yield, the second set of hybrids (RHB 233, RHB 234, AHB 1269, HHB 311) released in 2019–20 had 83–91 mg/kg Fe and 39–46 mg/kg Zn.